Analisis Rasio Likuiditas dan Rasio Profitabilitas untuk Menilai Kinerja Keuangan pada PT. Ultrajaya Milk Industry & Trading Company, Tbk. Periode 2020-2023 - Dhini Rusminah; Giantoro Pamungkas; Ira Karlisa; Azis Adelestari; Dina Rahmah Yani; Bilqis Fitri Ababil; Siti Kholisah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study is to determine the financial performance of PT Ultrajaya Milk Industry & Trading Company Tbk for the period 2020-2023 using financial ratios, namely liquidity ratio and profitability ratio. Data analysis uses a quantitative descriptive approach. The type of data obtained is secondary data. The data obtained is financial statements. The researchers obtained financial statement data from the IDX website. The results show that the company's liquidity is very good because the Current Ratio and Quick Ratio values ​​are above the industry norm. However, the company's profitability is considered poor, because the Return on Assets and Return on Equity values ​​are below the industry standard.